The representation of social changes in Indonesian Muslim society: a semiotic analysis of ‘Ketika Mas Gagah Pergi’ - Muh. Bahruddin; Ibnu Hamad; Triputra, Pinckey (Penerbit Universiti Kebangsaan Malaysia, 2021)
This research investigates the social changes concerning Islam's revitalisation, which was constructed by the movie Ketika Mas Gagah Pergi (KMGP). The research criticises structuration theory, which does not accommodate religion as part of social changes, especially in making new social changes. The researcher utilised semiotic logic by using the process of meaning or signification, which comprises signs or representation, object, and interpretant. The researcher also conducted in-depth interviews with filmmakers to understand the context from which the texts were produced. As a result, it was discovered that KMGP utilised signs to construct social changes through the act of wearing a veil, Islamic religious music, and the prohibition of shaking someone's hands which is not his/her mahram (legal spouse or guardian based on Islamic law), the separation of men and women in a wedding occasion, and other new rules which were previously not familiar in society. Nevertheless, to legitimise the new rules in these particular social practices, KMGP often used structure resources. For example, Gagah legitimated his action by referring to the tradition of Sundanese (one of the Indonesian tribes) to the prohibition of shaking a non-mahram’s hands. This is supported by hadith (speech, attitude, and behaviour of Prophet Muhammad) about this particular action. This movie also proved that the rules of Islamic religion became an important element that changed social order, especially in Indonesia.